Strain-Engineered MOSFETs - Maiti, C. K.; Maiti, T. K. (CRC Press, 2012)
This book brings together new developments in the area of strain-engineered MOSFETs using high-mibility substrates such as SIGe, strained-Si, germanium-on-insulator and III-V semiconductors into a single text which will cover the materials aspects, principles, and design of advanced devices, their fabrication and applications. The book presents a full TCAD methodology for strain-engineering in Si CMOS technology involving data flow from process simulation to systematic process variability simulation and generation of SPICE process compact models for manufacturing for yield optimization.
Description based on print version record.
KU Select 2018: STEM Backlist Books
Keywords: Technology & Engineering / Electronics / Microelectronics; Technology; Electronic books